2005
DOI: 10.1021/tx050082a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative Cytosine Deamination. An Exploration of the Chemistry Emanating from Deamination with Pyrimidine Ring-Opening

Abstract: A discussion of nitrosative deamination of cytosine 1 is presented that argues for the formation of 6 by diazotization of 1 to cytosinediazonium ion 2 and its electrostatic complex 3, dediazoniation to 4 <--> 5, and amide-bond cleavage to 6. The reaction channels available to 6 include hydrolytic deglycation to 3-isocyanatoacrylonitrile 7, water addition to carbamic acid 9 with the possibility for re-closure to uracil 13, water addition to carbamic acid 9, and decarboxylation to 3-aminoacrylonitrile 10. With a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…However, their reported activation energy [213 kJ mol -1 at B3LYP/6-31G(d)] was not very close to the experimentally accepted value (117 ( 4 kJ mol -1 ). 22, 23 Rayat et al studied the nitrosative deamination reactions of both guanine 24 and cytosine 25 and found several possible pathways, from which they proposed that the reactions proceed via a pyrimidine ringopened intermediate. For both guanine and cytosine, the intermediates were formed by dediazoniation and deprotonation of the guaninediazonium ion.…”
Section: Introductionmentioning
confidence: 99%
“…However, their reported activation energy [213 kJ mol -1 at B3LYP/6-31G(d)] was not very close to the experimentally accepted value (117 ( 4 kJ mol -1 ). 22, 23 Rayat et al studied the nitrosative deamination reactions of both guanine 24 and cytosine 25 and found several possible pathways, from which they proposed that the reactions proceed via a pyrimidine ringopened intermediate. For both guanine and cytosine, the intermediates were formed by dediazoniation and deprotonation of the guaninediazonium ion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that carbamic acid monoammonium salt is an important organic raw material of rubber auxiliary material, binder, UV absorbent, dyes, pharmaceuticals, explosives, etc. [30] . However, previous studies showed no data on the 2 urinary VOCs.…”
Section: Discussionmentioning
confidence: 99%
“…The proton affinity of 10 suggests that 10 and its isomers and conformers are formed in nitrosative cytosine deamination in aqueous solution. The possibility for recyclization of 10 to uracils has been explored experimentally and it is not likely [ 35 ]. Thus, toxicological studies of nitrosative cytosine deamination need to direct attention at 3-aminoacrylonitrile 9 and 3-isocyanatoacrylonitrile 10 .…”
Section: Discussionmentioning
confidence: 99%